ISLAM MADURA (Resistensi dan Adaptasi Tokoh Adat atas Penetrasi Kyai di Madura) - Hefni, Mohammad (Analisis: Jurnal Studi Keislaman, 2013)
Islam is a universal religion. The basic value of Islam implies a dialectical  relationship  of Islam and local culture.  Various study on Islam and local culture view traditional Islam, which is represented by the NU, as a single entity. The traditional Islam opposed to official Islam, and on the other hand it is confronted with  syncretic  Islam.  In Madura,  NU is not  a single entity. There are variation in it,  namely  a community  of traditional- acculturative Islam led by kyais and a community of traditional- syncretic Islam led by adat leaders. The latter community practices a ritual which is the ancestral tradition,  namely  the ritual of beberten. This ritual, according to the kyais, is seen as a syncretic ritual. Therefore, kyais penetrate to the adat community through bahs al-masa’il ad-diniyah and socialize it. Responding to  such penetration,  the  adat  community,  culturally,  applies resistance and adaptation  strategies.  Resistance is applied by revitalizing ritual of beberten, while adaptation  is applied by negating certain ritual elements, changing the meaning of ritual, and adding certain rituals.